2014
DOI: 10.1039/c4cp00977k
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylcyclopentadiene: time-resolved photoelectron spectroscopy and ab initio multiple spawning simulations

Abstract: Time-resolved photoelectron spectroscopy and ab initio multiple spawning dynamical simulations of hexamethylcyclopentadiene reveal wavepacket evolution in a distinct degree of freedom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 60 publications
(127 reference statements)
2
45
0
Order By: Relevance
“…30 In contrast to previous work, TDDFT-SH shows that the reaction dynamics take place on a single excited state only, which is similar to previous findings on cyclopenta-1,3-diene where another method (MS-MR-CASPT2) was used. 47,48 After excitation, the molecule stretches the For the hexatriene ground state, the simulations allowed us to follow the dynamics for 5 ps and we found that, after the Woodward-Hoffmann allowed conrotatory ring-opening, the tZt conformer is formed within 200 fs while the other conformers are formed afterwards, in slight disagreement with earlier work based on Ehrenfest dynamics simulations. 15 Therefore, more work will be necessary to disentangle the ground state rearrangements on a 100 femtosecond time scale.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…30 In contrast to previous work, TDDFT-SH shows that the reaction dynamics take place on a single excited state only, which is similar to previous findings on cyclopenta-1,3-diene where another method (MS-MR-CASPT2) was used. 47,48 After excitation, the molecule stretches the For the hexatriene ground state, the simulations allowed us to follow the dynamics for 5 ps and we found that, after the Woodward-Hoffmann allowed conrotatory ring-opening, the tZt conformer is formed within 200 fs while the other conformers are formed afterwards, in slight disagreement with earlier work based on Ehrenfest dynamics simulations. 15 Therefore, more work will be necessary to disentangle the ground state rearrangements on a 100 femtosecond time scale.…”
Section: Discussionsupporting
confidence: 40%
“…While the involvement of this state in the photodynamical trajectories seems to be well established in the case of open chained molecules, 71, 72 this is not necessarily so for cyclic dienes as inferred before for the case of CPD. 47,48 For CHD, we also find evidence for just one excited state in the reaction path, both through our photoelectron spectra and our ab initio calculations. Along the reaction coordinate, the character of the excited states changes, which was observed in earlier studies of CHD 30,73 but is also known from other small dienes that exhibit large amplitude motions such as butadiene 72 or CPD.…”
Section: Comparison With Literaturementioning
confidence: 65%
See 1 more Smart Citation
“…This shift is a sign of large amplitude motion experienced by photoexcited molecule and caused by both the rise of the vertical ionization potential along the large amplitude deformation coordinates and the conversion of potential energy into kinetic energy of the molecule. 48,49 In the present case, treating time zero as an additional fitting parameter yields a shift by 14 ± 6 fs. The decay-associated spectra (DAS) and the visualization of time zero fitting parameters are plotted in the Supporting Information ( Figure SI2).…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Ionization is also the first step in the high-harmonic generation of XUV and soft X-ray attosecond pulses, [8][9][10][11] and has been used as a tool for imaging molecular orbitals, [12][13][14][15] since the angular distribution of the ionization yield reflects the shape of the original molecular orbital. 16 A broadband superposition of valence excited states of the cation is prepared and monitored.…”
Section: Introductionmentioning
confidence: 99%